Recent advances of eosinophils and its correlated diseases - Tao, Zhang; Zhu, Hua; Zhang, Jiateng; Huang, Zhiming; Xiang, Ze; Hong, Tu (Frontiers in Public Health, 2022)
Human eosinophils exhibit unique multi-leaf nuclear morphology, which are filled with cytoplasmic granules that contain cytotoxicity and immune regulatory proteins. In recent years, it has been discovered that the eosinophils have the regulatory functions of innate and adaptive immunity and play an important role in asthma, chronic obstructive pulmonary diseases, acute respiratory distress syndrome and malignant tumors. In this review, we start from the perspective of eosinophil physiological function. Its developmental-related molecular mechanism, granule protein composition, and pathophysiological functions are also comprehensively elucidated. To conclude, the guiding significance of future disease treatment is proposed based on the recent updated understandings into the cell functions of eosinophils.